Analysis of Mathematical Connection Skills Using Realistic Mathematical Education (Indo-MathEdu Intellectuals Journal, 2021)
Connection ability is the ability to associate between topics in mathematics, associate mathematics in other sciences, and with everyday life. This research aims to find out the ability of mathematical connections by using the realistic mathematical education of the concept of Social Arithmetic in class VII of SMP Negeri 209 Jakarta. This type of research is qualitative descriptive with the selection of subjects based on the results of interviews. The main instrument in the study was the researchers themselves. Instruments for discovering mathematical connection skills are tests and interviews. Data collection techniques with observation guidelines, tests, interviews, and documentation. Data analysis used is qualitative analysis i.e. data collection, presentation of data, and withdrawal of conclusions. The results of the analysis showed that subjects included students who had the ability of mathematical connections that met 4 indicators of mathematical connections, namely recognizing the equivalent representation of the same concept, recognizing the relationship of a mathematical procedure of a representation to an equivalent representation procedure, using and assessing the relationship between topics with other disciplines, using mathematics in everyday life